2021
DOI: 10.1038/s41467-021-20894-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term single-cell imaging and simulations of microtubules reveal principles behind wall patterning during proto-xylem development

Abstract: Plants are the tallest organisms on Earth; a feature sustained by solute-transporting xylem vessels in the plant vasculature. The xylem vessels are supported by strong cell walls that are assembled in intricate patterns. Cortical microtubules direct wall deposition and need to rapidly re-organize during xylem cell development. Here, we establish long-term live-cell imaging of single Arabidopsis cells undergoing proto-xylem trans-differentiation, resulting in spiral wall patterns, to understand microtubule re-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(172 citation statements)
references
References 54 publications
8
153
3
Order By: Relevance
“…Therefore, KTN1 is not required for the cell-autonomous activity of miR165/6. KTN1-regulated microtubule organization was reported to be required for the spiral cell wall thickening in the protoxylem (Schneider et al, 2021). Our results here showed that expression of MIR165A in the stele results in ectopic formation of protoxylem cell wall patterns in the ktn1-20 background, which suggests that KTN1"s role in protoxylem cell wall patterning is likely indirect, properly through its regulation of xylem cell fates via miR165/6.…”
Section: Ktn1 Is Dispensable For the Cell Autonomous Activity Of Mir165/6supporting
confidence: 49%
“…Therefore, KTN1 is not required for the cell-autonomous activity of miR165/6. KTN1-regulated microtubule organization was reported to be required for the spiral cell wall thickening in the protoxylem (Schneider et al, 2021). Our results here showed that expression of MIR165A in the stele results in ectopic formation of protoxylem cell wall patterns in the ktn1-20 background, which suggests that KTN1"s role in protoxylem cell wall patterning is likely indirect, properly through its regulation of xylem cell fates via miR165/6.…”
Section: Ktn1 Is Dispensable For the Cell Autonomous Activity Of Mir165/6supporting
confidence: 49%
“…Notably, and in contrast to phytohormoneinduced systems [71,81,117], these systems specifically produces only protoxylem and metaxylem vessel-like elements, respectively [78]. The synchronized differentiation of cells into protoxylem/metaxylem vessels has allowed researchers to analyze the changes in the transcriptome [116,118], metabolome [118,119] and cellular dynamics of SCW formation [118,[120][121][122][123][124][125][126].…”
Section: Inducible Vnd Systems To Study Secondary Cell Wall Developmentmentioning
confidence: 99%
“…The different types of wall patterns are probably premediated by those forming in, or at, the plasma membrane. Such changes are thought to occur before changes in the microtubule networks become visible and the cell wall machinery is expressed and delivered to the plasma membrane [121,122,126]. Small GTPase proteins have proven critical in de novo formation of membrane patterns in many different organisms [130,[168][169][170].…”
Section: Patterning the Plasma Membranementioning
confidence: 99%
“…The cytoskeleton is also important for cell wall differentiation, which has been studied using a variety of systems, including transient expression in N. benthamiana leaves and in differentiating xylem (Oda and Fukuda, 2012;Oda, 2015). Of note, a cellular system was recently established to study longterm microtubule rearrangements occurring during proto-xylem development (Schneider et al, 2021). This system, based on xylem trans-differentiation upon induction of the transcription factor VASCULAR-RELATED NAC DOMAIN7 (VND7), allows microtubule dynamics to be followed at high temporal resolution and over the course of several hours.…”
Section: Model Systems For Live Imaging Of the Cytoskeletonmentioning
confidence: 99%
“…Using color-coded image sequence in the widely used image analysis software ImageJ (Schindelin et al, 2012;Schneider et al, 2012), the shift in the positions of bundles in interphasic cells can be visualized (Kuběnová et al, 2021). This post-acquisition analysis can be coupled with the generation of a kymograph, depicting straight lines when the cytoskeleton is immobile and wavy lines in the case of active movements (Lindeboom et al, 2013;Doumane et al, 2021;Schneider et al, 2021). The degree of bundling of the cytoskeleton in normalized image stacks can be obtained in a semi-automated way, using a plot profile generated from the Gel Analyser ImageJ function (Molines et al, 2018).…”
Section: Quantification Of Cytoskeleton Dynamics In Live Imaging Experimentsmentioning
confidence: 99%